STRATEGI PELANGGARAN TERHADAP MAKSIM SOPAN SANTUN YANG MEMUNCULKAN UNSUR HUMOR DALAM INDONESIA LAWAK KLUB - Fahmia, Nurul; Sopiahasnah, Siti; Firmansyah, Dida (IKIP Siliwangi, 2018)
This study aims to identify a violation strategy against the maxim of manners that can bring the element of laughter. The theory used is Geoffrey Leech's theory of the maxim of manners. The subject of this study was the Indonesian Club Lawak (ILK) show which was aired on March 13, 2014 with the theme of Dangdut Vs Rock in Trans 7. As the limitation of the problem, Komeng speech was analyzed against Deni Chandra, the host, and Cak Lontong, likes to provide invalid data and make everyone 's' annoyed', especially the host. The results of the study explain that there are four maxims that are violated, namely Maxim Sympathy Maxim (Maxim), Maksim Kearifan (Text Maxim), Maksim Pujian (Apribation Maxim), and Maximize Agreement (Agreement Maxim).